Compulsory Citizenship Behavior and Employee Creativity: Creative Self-Efficacy as a Mediator and Negative Affect as a Moderator - He, Peixu; Zhou, Qiongyao; Zhao, Hongdan; Jiang, Cuiling; Wu, Yenchun Jim (Frontiers in Psychology, 2020)
Workplace stressors were identified to have critical impacts on employee creativity. However, little is known about how and when involuntary citizenship behavior (i.e., compulsory citizenship behavior, CCB)-induced stress might exert influence on employee creativity. To fill this void, the present study firstly develops a moderated mediation model to investigate the CCB—employee creativity association as well as the underling mechanism and contextual condition of this relationship. By integrating social cognitive theory such as self-efficacy theory and conservation of resources (COR) theory, we propose that CCB predicts employee creativity through the mediating role of creative self-efficacy (CSE), with the individual characteristics (i.e., personality traits) of negative affect acting as a boundary condition. Using two-wave time-lagged survey data collected from a sample of 251 front-line employees in 10 manufacturing firms in Southern China, the results show that: (a) CSE mediates the negative relationship between CCB and employee creativity; (b) negative affect moderates the relationship between CCB and CSE; (c) negative affect moderates the indirect influence of CCB on employee creativity through CSE. As the level of negative affect rises, this indirect relationship is stronger. Finally, important theoretical and managerial implications and promising avenues for future research are addressed.